A high solid cathode slurry and a preparation method thereof

By optimizing the cathode slurry formulation and stirring process, and using single-walled CNTs as a conductive agent, high-solids-content cathode slurry can be properly coated in the battery, improving battery energy density and production efficiency while reducing solvent pollution.

CN115706212BActive Publication Date: 2026-11-06SHENZHEN MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110932300.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-13
Publication Date
2026-11-06
Estimated Expiration
2041-08-13

AI Technical Summary

Technical Problem

Existing cathode slurries cannot simultaneously increase solid content and maintain normal coating effect, resulting in low battery energy density, low production efficiency and poor ion conductivity.

Method used

A high-solids-content cathode slurry formulation is adopted, including cathode powder, conductive agent single-walled CNT, binder PVDF and solvent NMP. By optimizing the ratio and stirring process, the amount of solvent is reduced and the amount of conductive agent is increased, achieving a high-solids-content coating of more than 80%.

Benefits of technology

Achieving normal coating at high solids content improves battery energy density and production efficiency, reduces solvent contamination, and enhances electrode conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115706212B_ABST
    Figure CN115706212B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high solid positive electrode slurry and preparation method thereof, wherein, a kind of high solid positive electrode slurry, including positive electrode powder, conductive agent, binder and solvent;With positive electrode powder weight, the amount of conductive agent is 0.6% to 1%, the amount of binder is 0.5% to 1%, and theoretical solid content is greater than or equal to 80%.The high solid positive electrode slurry provided by the application can reduce the amount of solvent while not affecting the coating effect by reducing the amount of conductive agent, thereby achieving the purpose of normal coating operation under higher solid content, i.e., it can be effectively coated on the current collector when the theoretical solid content is greater than or equal to 80%, and the effect is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of batteries, and more specifically to a high-solids-content cathode slurry and its preparation method. Background Technology

[0002] Traditional cathode slurry formulations typically include cathode powder, conductive agent, binder, and solvent. The cathode powder is lithium manganese oxide, lithium cobalt oxide, or lithium nickel cobalt manganese oxide; the conductive agent is SP, GF-2, GF-6, or single-walled CNTs, etc.; the binder is an 8% (w / w) PVDF solution; and the solvent is an NMP solution. In cathode slurry preparation, the cathode powder and binder are first baked, and then the baked binder and solvent are combined into a binder. The baked cathode powder, conductive agent powder, binder binder solution, and solvent are then stirred together, following a principle of slow mixing followed by rapid dispersion. To meet coating requirements, the solid content is generally controlled between 65% and 75%. When the cathode powder is lithium manganese oxide or lithium cobalt oxide, the ratio of cathode powder: conductive agent: binder: solvent is 100:1.5:1.0:32.9, and the maximum conventional solid content is 75%; when the cathode powder is lithium nickel cobalt manganese oxide, the ratio of cathode powder: conductive agent: binder: solvent is 100:1.5:1.0:42.6, and the maximum conventional solid content is 70%.

[0003] The above solid content is a theoretical solid content value obtained from theoretical calculations. The formula for calculating the theoretical solid content value is: Theoretical solid content value = (m powder + m conductive agent + m binder * 8%) / (m powder + m conductive agent + m binder + m solvent) * 100%.

[0004] As those skilled in the art know, if the solid content is low, the corresponding solvent addition is relatively high, resulting in a lower content of effective materials and a correspondingly lower energy density of the battery. At the same time, due to the higher solvent content, the drying time of the electrode is relatively longer, which reduces the actual production efficiency. Furthermore, the contact area between the current collector and the active material is slightly smaller, and the ion conductivity is lower than that of a battery with a high solid content.

[0005] Therefore, in order to increase the solid content, the conventional approach for those skilled in the art is to directly reduce the amount of solvent. However, reducing the amount of solvent makes it impossible to achieve proper coating. Consequently, existing cathode slurries cannot simultaneously achieve both increased solid content and proper coating. Summary of the Invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing cathode slurries that cannot simultaneously meet the requirements of increasing solid content and normal coating, and to provide a high solid content cathode slurry and its preparation method that can be normally coated even with a high solid content of more than 80%.

[0007] A high-solids-content positive electrode slurry includes positive electrode powder, conductive agent, binder and solvent; based on the weight of the positive electrode powder, the amount of conductive agent is 0.6%-1%, the amount of binder is 0.5%-1%, and the theoretical solids content is ≥80%.

[0008] The cathode powder includes at least lithium cobalt oxide.

[0009] The cathode powder also includes lithium manganese oxide or lithium nickel cobalt manganese oxide, and the content of lithium cobalt oxide in the cathode powder is higher than 50 wt%.

[0010] The conductive agent is a single-walled CNT.

[0011] The single-walled CNT has a diameter of 0.7-2 nm and a length of 20-50 μm.

[0012] The binder is PVDF, and the solvent is NMP.

[0013] The PVDF has a crystallinity of 65%-78%, a density of 1.77-1.80 g / cm3, and a melting point of 170℃-172℃.

[0014] The theoretical solid content is 80%-85%, preferably 83%-85%.

[0015] A method for preparing a high-solids-content cathode slurry, comprising:

[0016] Dry the positive electrode powder and binder, and mix the dried binder with a solvent to prepare a binder solution; measure the positive electrode powder, binder solution, conductive agent and solvent according to the above-mentioned high solids content positive electrode slurry ratio; stir and mix evenly and then disperse.

[0017] During the mixing process, the positive electrode powder is divided into at least two parts and added in batches. The first addition of the positive electrode powder includes all the conductive agent and solvent.

[0018] The stirring speed for mixing is 30-45 Hz, and the stirring speed for dispersion is 120-150 Hz.

[0019] The adhesive solution has a mass concentration of 8%.

[0020] The technical solution of this invention has the following advantages:

[0021] 1. The present invention provides a high solids content positive electrode slurry, which reduces the amount of conductive agent used, thereby reducing the amount of solvent used without affecting the coating effect. This allows for normal coating operation even with higher solids content, meaning that it can be effectively and normally coated on the current collector even when the theoretical solids content reaches ≥80%, with significant effect.

[0022] Furthermore, since this invention reduces the use of solvents, which are toxic and volatile, it can reduce environmental pollution and lower costs. Simultaneously, the reduction in solvents increases the solid content of the slurry, allowing for faster electrode baking and improved manufacturing efficiency. Moreover, the high solid content of the slurry effectively increases the amount of active material per unit area, thus improving the battery's energy density. Additionally, the increased contact area between the active material and the current collector during coating significantly enhances the cell's conductivity.

[0023] 2. This invention further optimizes the type of conductive agent. When using single-walled CNTs as a conductive agent, due to their superior conductivity, they not only achieve better conductivity at the same ratio, but also significantly increase the theoretical solid content while ensuring coating effect. Compared with other conductive agents such as SP, the theoretical solid content can be increased from 80% to 84%. Moreover, the use of single-walled CNTs has the advantage that the actual solid content is closer to the theoretical solid content, making its effect even better.

[0024] 3. This invention is applicable to process design schemes with relatively low areal density. Attached Figure Description

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0026] Figure 1 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 84% obtained in Example 1;

[0027] Figure 2 This is a diagram showing the effect of coating the high-solids-content positive electrode slurry of Example 1 onto the current collector;

[0028] Figure 3 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 80.5% obtained in Example 2;

[0029] Figure 4 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 84% obtained in Example 2;

[0030] Figure 5 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 82% obtained in Example 3;

[0031] Figure 6 This is a diagram showing the effect of applying the high-solids-content positive electrode slurry of Example 3 onto the current collector;

[0032] Figure 7 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 80% obtained in Example 4;

[0033] Figure 8 This is a diagram showing the effect of coating the high-solids-content cathode slurry with a theoretical solids content of 80% onto the current collector in Example 4.

[0034] Figure 9 This is a finished product image of the high solids content cathode slurry with a theoretical solids content of 82% obtained in Example 4;

[0035] Figure 10 This is a diagram showing the effect of applying the high solids content positive electrode slurry with a theoretical solids content of 82% to the current collector in Example 4. Detailed Implementation

[0036] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0037] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0038] Example 1

[0039] A high-solids-content cathode slurry comprises cathode powder, a conductive agent, a binder solution, and a solvent in a mass ratio of 100:0.83:0.8. In this embodiment, the cathode powder is composed of lithium cobalt oxide and lithium manganese oxide, with lithium cobalt oxide comprising 80% of the total weight of the cathode powder. The conductive agent is single-walled CNTs; in this embodiment, a commercially available single-walled CNT product with a solids content of 28.5% is used. The single-walled CNTs in this product have a diameter of 0.7-2 nm and a length of 20-50 μm. The binder is PVDF, with a crystallinity of 65%-78% and a density of 1.77-1.80 g / cm³. 3 Melting point is 170℃-172℃; solvent is NMP.

[0040] The specific preparation method of the above-mentioned high solids content cathode slurry is as follows:

[0041] (1) Dry the positive electrode material and binder first, bake at 120 degrees Celsius for 2 hours;

[0042] (2) The baked adhesive and NMP are mixed in a mixing tank. After stirring, an adhesive solution is obtained. The solid content of the mixed adhesive solution is 8%. The stirring parameters of the mixing tank are 25-35 Hz revolution and 35-45 Hz rotation. Vacuum is required during the stirring process. The stirring time is 2-4 hours. The adhesive solution obtained by stirring is sealed with a film.

[0043] (3) Weigh according to the ratio of positive electrode powder: single-walled CNT: binder = 100: 0.83: 0.8; based on weighing 100g of positive electrode powder, it is necessary to weigh 80g of lithium cobalt oxide, 20g of lithium manganese oxide, 0.83g / 28.5% = 2.91g of single-walled CNT product, and 0.8g / 8% = 10g of binder solution.

[0044] (4) Weigh different amounts of solvent NMP. Add different amounts of solvent NMP, positive electrode powder, single-walled CNT product, and binder solution to a mixer. First, mix at 30 Hz for 0.5 h, then disperse at 150 Hz for 10 min, and then mix at 45 Hz for 0.5 h to prepare high solids content positive electrode slurries with different theoretical solid contents.

[0045] (5) A 100-150 mesh scraper is used to coat the high-solids-content cathode slurry onto the current collector. When the minimum content of the solvent NMP is 8.08% of the cathode powder content, normal coating of the high-solids-content cathode slurry can be achieved. Taking 100g of powder as an example, the theoretical solids content of this high-solids-content cathode slurry = (mpowder100g + msingle-walled CNT0.83g + mPVDF0.8g) / (mpowder100g + msingle-walled CNT0.83g / 0.285 + mPVDF0.8g / 0.08 + msolventNMP 8.08g) = 84%. In this embodiment, the high-solids-content cathode slurry with a theoretical solids content of 84% is as follows: Figure 1 As shown, the result after coating on the current collector is as follows: Figure 2 As shown.

[0046] In this embodiment, the high solids content cathode slurry is also suitable for process design schemes with relatively low areal density.

[0047] Example 2

[0048] A high-solids-content cathode slurry differs from Example 1 in that the conductive agent used in this example is different; SP is used instead. Otherwise, it is the same as Example 1. With this type of conductive agent, high-solids-content cathode slurries with different theoretical solid contents are prepared. When the minimum content of the solvent NMP is 15.4% of the cathode powder content, normal coating of the high-solids-content cathode slurry can be achieved. In this case, based on 100g of powder, the theoretical solid content of the high-solids-content cathode slurry = (mpowder100g + mSP0.83g + mPVDF0.8g) / (mpowder100g + mSP0.83g + mPVDF0.8g / 0.08 + msolventNMP 15.4g) = 80.5%. In this example, the high-solids-content cathode slurry with a theoretical solid content of 80.5% is as follows: Figure 3 As shown. In this embodiment, the theoretical solid content is 84% ​​when the amount of solvent NMP is further reduced to 10.2%. The high solid content cathode slurry under this theoretical solid content is as follows: Figure 4 As shown, at this point, the high-solids-content cathode slurry cannot be properly coated.

[0049] Example 3

[0050] A high-solids-content cathode slurry differs from Example 1 in that the cathode powder used in this example is different. In this example, the cathode powder includes lithium cobalt oxide and lithium nickel cobalt manganese oxide, with the lithium cobalt oxide content being 50% of the total weight of the cathode powder. Other aspects are the same as in Example 1. Under this type of cathode powder composition, high-solids-content cathode slurries with different theoretical solid contents are prepared. When the minimum content of the solvent NMP is 11.03% of the cathode powder content, normal coating of the high-solids-content cathode slurry can be achieved. At this point, taking 100g of powder as the unit, the theoretical solid content of this high-solids cathode slurry is calculated as follows: (mpowder100g + msingle-walled CNT0.83g + mPVDF0.8g) / (mpowder100g + msingle-walled CNT0.83g / 0.285 + mPVDF0.8g / 0.08 + msolventNMP11.03g) = 82%. In this embodiment, the high-solids cathode slurry with a theoretical solid content of 82% is as follows: Figure 5 As shown, the application effect is as follows Figure 6 As shown.

[0051] Example 4

[0052] A high-solids-content cathode slurry differs from Example 1 in that the cathode powder used in this example is different. In this example, the cathode powder includes lithium cobalt oxide and lithium nickel cobalt manganese oxide, with the lithium cobalt oxide content being 50% of the total weight of the cathode powder. Furthermore, the conductive agent used in this example is SP, while other aspects are the same as in Example 1. Under this composition of cathode powder and conductive agent, high-solids-content cathode slurries with different theoretical solid contents were prepared. When the minimum content of the solvent NMP is 16.2% of the cathode powder content, normal coating of the high-solids-content cathode slurry can be achieved. At this point, taking 100g of powder as the unit, the theoretical solid content of this high-solids cathode slurry is calculated as follows: (mpowder100g + mSP0.83g + mPVDF0.8g) / (mpowder100g + mSP0.83g + mPVDF0.8g / 0.08 + msolventNMP 16.2g) = 80%. In this embodiment, the high-solids cathode slurry with a theoretical solid content of 80% is as follows: Figure 7 As shown, the application effect is as follows Figure 8 As shown. In this embodiment, the theoretical solid content is 82% when the amount of solvent NMP is further reduced to 13.1%. The high solid content cathode slurry under this theoretical solid content is as follows: Figure 9 As shown, the application effect is as follows Figure 10 As shown, it can be demonstrated that normal coating of the positive electrode slurry cannot be achieved under this theoretical solid content.

[0053] Example 5

[0054] A high-solids-content cathode slurry comprises cathode powder, a conductive agent, a binder solution, and a solvent in a mass ratio of 100:0.6:1. In this embodiment, the cathode powder is lithium cobalt oxide; the conductive agent is single-walled CNTs, specifically a commercially available single-walled CNT product with a solids content of 28.5% used in Example 1; the binder is PVDF; and the solvent is NMP.

[0055] The specific preparation method of the above-mentioned high solids content cathode slurry is as follows:

[0056] (1) Dry the positive electrode material and binder first, bake at 120 degrees Celsius for 2 hours;

[0057] (2) The baked adhesive and NMP are mixed in a mixing tank. After stirring, an adhesive solution is obtained. The solid content of the mixed adhesive solution is 8%. The stirring parameters of the mixing tank are 25-35 Hz revolution and 35-45 Hz rotation. Vacuum is required during the stirring process. The stirring time is 2-4 hours. The adhesive solution obtained by stirring is sealed with a film.

[0058] (3) Weigh according to the ratio of positive electrode powder: single-wall CNT: binder = 100: 0.6: 1; based on weighing 100g of positive electrode powder, it is necessary to weigh 100g of lithium cobalt oxide, 0.6g / 28.5% = 2.1g of single-wall CNT product, and 1g / 8% = 12.5g of binder solution.

[0059] (4) Weigh out 9.2% of the positive electrode powder with NMP solvent. Add the NMP solvent, half of the positive electrode powder, all of the single-walled CNT product and all of the binder solution into a mixer. First, mix at 45 Hz for 0.5 h to ensure homogeneity. Then add the remaining positive electrode powder and mix for 0.5 h. After mixing, disperse at 120 Hz for 14 min. Finally, mix at 35 Hz for 0.5 h to prepare a high solids content positive electrode slurry with a theoretical solids content of 82%.

[0060] (5) A 100-150 mesh scraper is used to coat the high solids content positive electrode slurry on the current collector, and the coating can be carried out smoothly.

[0061] Example 6

[0062] A high-solids-content cathode slurry comprises cathode powder, a conductive agent, a binder solution, and a solvent in a mass ratio of 100:1:0.5. In this embodiment, the cathode powder is lithium cobalt oxide; the conductive agent is single-walled CNTs, specifically a commercially available single-walled CNT product with a solids content of 28.5% used in Example 1; the binder is PVDF; and the solvent is NMP.

[0063] The specific preparation method of the above-mentioned high solids content cathode slurry is as follows:

[0064] (1) Dry the positive electrode material and binder first, bake at 120 degrees Celsius for 2 hours;

[0065] (2) The baked adhesive and NMP are mixed in a mixing tank. After stirring, an adhesive solution is obtained. The solid content of the mixed adhesive solution is 8%. The stirring parameters of the mixing tank are 25-35 Hz revolution and 35-45 Hz rotation. Vacuum is required during the stirring process. The stirring time is 2-4 hours. The adhesive solution obtained by stirring is sealed with a film.

[0066] (3) Weigh according to the ratio of positive electrode powder: single-walled CNT: binder = 100: 1: 0.5; based on weighing 100g of positive electrode powder, it is necessary to weigh 100g of lithium cobalt oxide, 1g / 28.5% = 3.5g of single-walled CNT product, and 0.5g / 8% = 6.3g of binder solution.

[0067] (4) Weigh out 14% of the solvent NMP by weight of the positive electrode powder. Add the solvent NMP, positive electrode powder, single-walled CNT product, and binder solution into a mixer. First, mix at 40 Hz for 0.5 h to achieve uniformity. Then, disperse at 140 Hz for 12 min and then mix at 40 Hz for 1 h to prepare a high solids content positive electrode slurry with a theoretical solids content of 82%.

[0068] (5) A 100-150 mesh scraper is used to coat the high solids content positive electrode slurry on the current collector, and the coating can be carried out smoothly.

[0069] Comparative Example 1

[0070] A high-solids-content positive electrode slurry differs from Example 1 in that the type and amount of conductive agent used in this example are different. The conductive agent used in this example is a conventional multi-walled CNT with a tube diameter of 4-6 nm, and the amount of multi-walled CNT is 1.4%, that is, the mass ratio of positive electrode powder, conductive agent and binder is 100:1.5:0.8; otherwise, it is the same as Example 1. The high-solids-content positive electrode slurry with a theoretical solids content of 80% is prepared using the solvent NMP. When the high-solids-content positive electrode slurry is applied to the current collector using a 100-150 mesh doctor blade, it is found that normal application cannot be achieved.

[0071] Test case

[0072] The actual solid content of the high-solids-content cathode slurry with the highest theoretical solid content described in Examples 1-4 was tested. The testing process was as follows: the foil was folded into a square, and the mass M1 was weighed using an analytical balance. Then, a small amount of the prepared cathode slurry was evenly coated on the foil, and the mass M2 was weighed. The foil was baked at a temperature of 90-100℃ for 30 minutes, and then weighed M3. The actual solid content value = (M3-M1) / (M2-M1).

[0073] The actual solid content values ​​of Examples 1-5 obtained by the above method are shown in Table 1 below.

[0074] Table 1

[0075] Theory inherent Actual solid content Example 1 84.0% 83.7% Example 2 80.5% 80.0% Example 3 82.0% 81.8% Example 4 80.0% 79.0%

[0076] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A high-solids-content positive electrode slurry, comprising positive electrode powder, conductive agent, binder, and solvent; characterized in that, Based on the weight of the positive electrode powder, the amount of conductive agent is 0.6%-1.0%, the amount of binder is 0.5-1.0%, and the theoretical solid content is ≥80%. The positive electrode powder includes lithium cobalt oxide; The cathode powder further includes lithium manganese oxide or lithium nickel cobalt manganese oxide, wherein the content of lithium cobalt oxide in the cathode powder is ≥50 wt%; The conductive agent is a single-walled CNT with a diameter of 0.7-2 nm and a length of 20-50 μm; the binder is PVDF and the solvent is NMP.

2. The high-solids-content positive electrode slurry according to claim 1, characterized in that, The PVDF has a crystallinity of 65%-78% and a density of 1.77-1.80 g / cm³. 3 Its melting point is 170℃-172℃.

3. The high-solids-content positive electrode slurry according to claim 1, characterized in that, The theoretical solid content is 80%-85%.

4. The high-solids-content positive electrode slurry according to claim 3, characterized in that, The theoretical solid content is 83%-85%.

5. A method for preparing a high-solids-content cathode slurry according to any one of claims 1-4, characterized in that, include: The positive electrode powder and binder are dried, and the dried binder is mixed with a solvent to prepare a binder solution. According to any one of claims 1-4, the high solids content positive electrode slurry is prepared by measuring the positive electrode powder, binder solution, conductive agent and solvent in the specified proportions; after stirring and mixing evenly, it is dispersed.

6. The preparation method according to claim 5, characterized in that, During the mixing process, the positive electrode powder is divided into at least two parts and added in batches. The first addition of the positive electrode powder includes all the conductive agent and solvent.

7. The preparation method according to claim 5, characterized in that, The adhesive solution has a mass concentration of 8%.

Citation Information

Patent Citations

  • Lithium ion power battery with long service life and preparation method thereof

    CN106356556A

  • Carbon nanotube polymer lithium ion battery and preparation method thereof

    CN107195885A